Secession and Self-Determination NOMOS XLV (NOMOS - American Society for Political and Legal Philosophy, 2003)
The many questions that surround movements for secession and self-determination are both practically urgent and theoretically perplexing. The United States settled its secession crisis in the 1860s. But the trauma and unfinished business of those events are still with us. Around the world secession and self-determination are the key issues that cause strife and instability. This volume provides an unusually comprehensive consideration of the many challenges of law and political philosophy that accompany them, and offers theoretical insights that provide guidance for policy. Among the questions considered are: should the international community recognize a right to secede and, if so, what conditions must be satisfied before the right can be asserted? Should secession and its conditions be recognized within domestic constitutions? Secession is the most extreme form of political separation and there are modes of self-determination short of it, including indigenous peoples' self-government and minority language rights. To what degree can these intrastate autonomy arrangements help ameliorate the injustices faced by indigenous groups?